An integrated map of the genome of the tubercle bacillus, Mycobacterium tuberculosis H37Rv, and comparison with Mycobacterium leprae. - Philipp, W J (1996)
An integrated map of the genome of the tubercle bacillus, Mycobacterium tuberculosis, was constructed by using a twin-pronged approach. Pulsed-field gel electrophoretic analysis enabled cleavage sites for Asn I and Dra I to be positioned on the 4.4-Mb circular chromosome, while, in parallel, clones from two cosmid libraries were ordered into contigs by means of fingerprinting and hybridization mapping. The resultant contig map was readily correlated with the physical map of the genome via the landmarked restriction sites. Over 165 genes and markers were localized on the integrated map, thus enabling comparisons with the leprosy bacillus, Mycobacterium leprae, to be undertaken. Mycobacterial genomes appear to have evolved as mosaic structures since extended segments with conserved gene order and organization are interspersed with different flanking regions. Repetitive sequences and insertion elements are highly abundant in M. tuberculosis, but the distribution of IS6110 is apparently nonrandom.